Utilizing Bland and Interactive PowerPoint during Mathematics Class: Physical Education Students’ Perceptions - Mercado, Maria Crisella Dela Cruz; Calaguas, Krizzel B.; Vitug, Zhairel Mae O.; Castro, Abigail B.; Yumang, Mary Grace M.; Gaspar, Romalyn S.; Nucum, Rona G. (Brillo Journal, 2024)
PowerPoint is a widely used presentation software capable of displaying multimedia elements such as images, videos, audio, and text through visually engaging and creative slide shows. This study explored the perceptions of Physical Education students regarding the use of bland and interactive PowerPoint during their Mathematics classes. Specifically, it aimed to determine whether students’ perceptions varied in terms of active participation, motivation, and learning when exposed to these two types of PowerPoint presentations. The study involved 36 first-year Bachelor of Physical Education students at a university in Pampanga, Philippines, comprising 22 females and 14 males. Using a closed-ended questionnaire, quantitative data were collected and analyzed. The findings revealed a significant difference in students' perceptions, with more students strongly agreeing that interactive PowerPoint (iPPT) significantly enhanced their active participation, motivation, and learning compared to bland PowerPoint (bPPT). It was concluded that the use of iPPT in teaching Mathematics provided greater support to students, particularly by fostering higher levels of engagement, motivation, and improved learning outcomes.